Impact of Modern Digitization of Logistics Operations on Supply Chain Performance: A Case Study of Almarai Company, Saudi Arabia - Albalwy, Hanan Rashid (Journal of Economic, Administrative and Legal Sciences, 2025)
This study aims to analyze the impact of digitizing logistics operations, including transportation, storage, and delivery, on supply chain management performance at Almarai Company in Saudi Arabia. The study adopted a descriptive-analytical approach and used statistical analysis methods, including simple and multiple linear regression, to analyze data collected in 2024 through surveys and field interviews with managers and employees at the target company. The results showed a positive and statistically significant impact of digitizing transportation operations on supply chain performance. It was also found that digitizing storage and delivery operations contributes to performance improvement. When analyzing the overall impact of digitization through multiple linear regression, the results revealed that the digitization of logistics operations collectively explains about 33.5% of the changes in supply chain management performance, highlighting the strategic importance of digital transformation in this field. The study emphasized that the shift toward integrated digital systems in transportation, storage, and distribution contributes to enhancing supply chain flexibility, reducing waste, improving information flow, and increasing the company’s competitiveness. The results also underscored the importance of using technologies such as real-time tracking, smart inventory management systems, and advanced digital distribution platforms to achieve higher performance levels. Based on the findings, the study recommends the sustainable investment in digitizing all logistics operations, focusing on system integration and keeping them updated in line with global technological developments. It also recommends training and developing human resources to maximize the benefits of digital transformation and ensure operational sustainability while achieving long-term competitive advantages.